Development of Low-cost Layer Diets Using Local Resources for Promoting the Sustainable Self-reliance of Small-scale Farmers in the Tontan Sub-district, Suphan Buri Province, Thailand - Wathinputthiporn, Donchida; Sampaothong, Sonthaya; Ruangpanit, Yuwares; Pongmanee, Koonphol (Area Based Development Research Journal, 2024)
Small-scale laying hen farmers in the Tontan Sub-district, Song Phi Nong District, Suphan Buri Province of Thailand, face challenges due to limited knowledge and skills in feed formulation. They rely on expensive commercial feeds and incur additional transportation costs, resulting in high production expenses. This study aimed to develop cost-effective and sustainable feed formulations using local resources, specifically water spinach and stinking passionflower, to promote self-sufficiency and reduce production costs. The research involved collaboration between local corporate networks, small-scale farmers, educational institutions, and government organizations to: 1) establish community partnerships, assess farmers' needs, and build community capacity, 2) evaluate the potential of local resources, 3) develop and test laying hen diets, and 4) provide education and business strategies to foster self-sufficiency. Forty Lohmann Brown hens (75 weeks old) were raised in individual cages under an open housing system and divided into four groups (10 hens each). They were fed conventional, reference, stinking passionflower, and water spinach diets for 21 days. Results indicated that stinking passionflower and water spinach diets could be effective feed alternatives, showing trends toward increased egg weight (P = 0.087) and egg mass (P = 0.093) without negatively affecting egg quality. The stinking passionflower and water spinach diets also reduced feed costs by 2.25 Baht/kg and 2.20 Baht/kg, respectively (around 0.07 USD/kg). This initiative enabled farmers and local networks to produce and distribute affordable, locally sourced feeds within their communities, fostering a community-based circular economy. By driving the principles of the sufficiency economy, this model strengthens self-sufficiency and supports the sustainable development of the community’s foundational economy.